Institutional patterns, attitudes, knowledge and practices pertaining to sexual relations and birth control amongst the Cape Coloureds - Roux, Marianne Cornelia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1968.